Influence of Surgeon Volume on Inpatient Complications, Cost, and Length of Stay Following Total Ankle Arthroplasty. (October 2016) - Basques, Bryce A.; Bitterman, Adam; Campbell, Kevin J.; Haughom, Bryan D.; Lin, Johnny; Lee, Simon
Background: Increased surgeon volume may be associated with improved outcomes following operative procedures. However, there is a lack of information on the effect of surgeon volume on inpatient adverse events and resource utilization following total ankle arthroplasty (TAA). Methods: A retrospective cohort study of TAA patients was performed using the Nationwide Inpatient Sample (NIS) from 2003 to 2009. High-volume surgeons were considered as those with volume ≥90th percentile of surgeons performing TAA. Multivariate regression was used to compare the rates of adverse events, hospital length of stay, and total hospital charges between surgeon volume categories. Results: A total of 4800 TAA patients were identified. The 90th percentile for surgeon volume was 21 cases per year. Mean length of stay was 2.8 ± 2.3 days and mean hospital charges were $45 963 ± $43 983. On multivariate analysis, high-volume surgeons had decreased overall complications (OR 0.5, P = .034) and rate of medial malleolus fracture (OR 0.1, P = .043), decreased length of stay (–0.9 days, P < .001), and decreased hospital charges (–$20 904, P < .001). Conclusions: Surgeons with volume ≥90th percentile had a decreased rate of complications, decreased length of stay, and reduced hospital charges compared to other surgeons. Level of Evidence: Level III, comparative study.